Indoxyl Sulfate Contributes to Impaired Height Velocity in (Pre)School Children - Evelien Snauwaert; Stefanie De Buyser; Wim Van Biesen; Ann Raes; Griet Glorieux; Laure Collard; Koen Van Hoeck; Maria Van Dyck; Nathalie Godefroid; Johan Vande Walle; Sunny Eloot (Kidney International Reports)
Introduction: Growth failure is considered the most important clinical outcome parameter in childhood chronic kidney disease (CKD). Central to the pathophysiology of growth failure is the presence of a chronic proinflammatory state, presumed to be partly driven by the accumulation of uremic toxins. In this study, we assessed the association between uremic toxin concentrations and height velocity in a longitudinal multicentric prospective pediatric CKD cohort of (pre)school-aged children and children during pubertal stages. Methods: In a prospective, multicentric observational study, a selection of uremic toxin levels of children (aged 0–18 years) with CKD stage 1 to 5D was assessed every 3 months (maximum 2 years) along with clinical growth parameters. Linear mixed models with a random slope for age and a random intercept for child were fitted for height (in cm and SD scores [SDS]). A piecewise linear association between age and height was assumed. Results: Data analysis included data from 560 visits of 81 children (median age 9.4 years; 2/3 male). In (pre)school aged children (aged 2–12 years), a 10% increase in concurrent indoxyl sulfate (IxS, total) concentration resulted in an estimated mean height velocity decrease of 0.002 SDS/yr (P < 0.05), given that CKD stage, growth hormone (GH), bicarbonate concentration, and dietary protein intake were held constant. No significant association with height velocity was found in children during pubertal stages (aged >12 years). Conclusion: The present study demonstrated that, especially IxS contributes to a lower height velocity in (pre)school children, whereas we could not find a role for uremic toxins with height velocity during pubertal stages.